Eesti kirikute liikmeskonna usulised tõekspidamised ja praktikad uuringu „Elust, usust ja usuelust 2020“ tulemuste põhjal - Soom, Kaido (Usuteaduslik Ajakiri, 2024)
The aim of this article is to analyse the worldview of Estonian Christians based on the survey] „Life, Faith and Religion 2020“. Analysing the results of the survey, it is found that 22% of the Estonian population belongs to a congregation and the number of people belonging to Christian congregations is 19% of the Estonian population. Of those belonging to religious movements, 43% are Lutheran and 35% Orthodox. Lutherans are primarily Estonians and Orthodox Christians non-Estonians. Of the people belonging to a church, 26% were over 70 years old and 36% of Christians have a higher education. Among the respondents belonging to a congregation, 30% received a lot of religious knowledge at home, indicating that religious socialisation is still functioning. Half of the children of people belonging to the larger churches are unbaptised, indicating a break in socialisation. Furthermore, 81% of Christians believe in the existence of God. Acceptance of non-Christian doctrines has decreased significantly, especially among Christians. Explaining that 72% of Christians have experienced God’s guidance in their lives, with 33% praying daily and 18% attending weekly worship services. Both church members and non-church members expected above all that the church would talk about life and death and eternal issues. This survey shows that 43% of Christians actively participate in the Eucharist. More than three quarters of Christians attach importance to church Rites of passage.